Happiness as a state of consciousness - Tymofieiev, Oleksandr (Видавництво НТУ «ДП», 2020)
The importance of what people understand under the word "happiness" is difficult to put under doubt. The pursuit of happiness is inherent in every human being and is an integral part of human nature.Happiness is one of the main human values. However, the phenomenon of happiness eludes clear definitions and categorizations. In our article, we will try to consider the problem of happiness in the context of the state of consciousness.
Keywords: суспільна свідомість; свідомість